2014
DOI: 10.1158/0008-5472.can-14-1032
|View full text |Cite
|
Sign up to set email alerts
|

CD66+ Cells in Cervical Precancers Are Partially Differentiated Progenitors with Neoplastic Traits

Abstract: Cervical cancers, a malignancy associated with oncogenic papillomaviruses, remain a major disease burden in the absence of effective implementation of preventive strategies. CD66+ cells have previously been identified as a tumor propagating subset in cervical cancers. We investigated the existence, differentiation state and neoplastic potential of CD66+ cells in a pre-cancer cell line harboring HPV31b episomes. The gene expression profile of CD66High cells overlaps with differentiated keratinocytes, neoplastic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
(82 reference statements)
1
5
0
Order By: Relevance
“…Recent studies support our findings and have found increased Notch1 expression co-occurring with both an increased growth potential and differentiation marker expression in cervical cancer cell lines as well as in HFKs expressing HPV 31 (Pattabiraman, Hong et al, 2014). Additionally, the parsing of differentiation and growth arrest pathways has been seen in the context of 16E7 expression (Lefort, Mandinova et al, 2007; Muller, Alunni-Fabbroni et al, 1999; Nguyen, Lefort et al, 2006), so there is precedence for an HPV oncoprotein uncoupling differentiation from cellular growth.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies support our findings and have found increased Notch1 expression co-occurring with both an increased growth potential and differentiation marker expression in cervical cancer cell lines as well as in HFKs expressing HPV 31 (Pattabiraman, Hong et al, 2014). Additionally, the parsing of differentiation and growth arrest pathways has been seen in the context of 16E7 expression (Lefort, Mandinova et al, 2007; Muller, Alunni-Fabbroni et al, 1999; Nguyen, Lefort et al, 2006), so there is precedence for an HPV oncoprotein uncoupling differentiation from cellular growth.…”
Section: Discussionsupporting
confidence: 91%
“…2 show that both in primary tissue and cervical cancer cell line model, the leading CD49f positive cells are more basal and proliferative; whereas trailing CD66 cells are more differentiated, migratory and show features of EMT. We have previously shown [7] using dye-dilution experiments that in whole CaSki-spheroids, CD66À CD49fþcells proliferate more compared to other subsets. Also we have shown [7] that CD66 and CD49f subsets follow a hierarchy in the expression of differentiation markers S100P and Involucrin in sorted cells from cell line and patient samples.…”
Section: Cd49f and Cd66 Subsets Associated With Distinct Neoplastic Tmentioning
confidence: 96%
“…We have previously shown [7] using dye-dilution experiments that in whole CaSki-spheroids, CD66À CD49fþcells proliferate more compared to other subsets. Also we have shown [7] that CD66 and CD49f subsets follow a hierarchy in the expression of differentiation markers S100P and Involucrin in sorted cells from cell line and patient samples. CD66þCD49fÀ cells express highest levels of S100P and involucrin, followed by CD66þCD49fþ cells and then the CD66ÀCD49fþve cells.…”
Section: Cd49f and Cd66 Subsets Associated With Distinct Neoplastic Tmentioning
confidence: 96%
See 1 more Smart Citation
“…A monoclonal antibody against CEACAM1 enhanced the effects of melanoma reactive lymphocytes in a mouse model of human melanoma xenograft (91). Precancerous lesions of the uterine cervix that harbor HPV genetic elements co-express CEACAM1, allowing for viral replication (92). Thus all TIM-3 ligands have multiple functions, besides inhibiting CTLs that affect various aspects of carcinogenesis.…”
Section: B7-h4 (Alternatively Called B7x or B7s1)mentioning
confidence: 99%